Inclusive and Extractive Institutions: A Reasonable Dichotomy? - Spliet, Bas (TSEG - The Low Countries Journal of Social and Economic History, 2024)
Prak and Van Zanden argue that these differences of political culture are deeply embedded in history. The premise of their book is that the Dutch economy has been dominated by markets for centuries, but, moving beyond the singular focus on property rights and representative institutions associated with authors of the new institutional economics (NIE), they argue that state intervention, particularly after 1600, “restrained the capitalist impulse” and improved “the stability of the system”. The authors thereby reinforce a crucial insight that the absence of these predatory institutions on European soil, or the emancipation of the middle classes for that matter, were not the product of intellectual or moral advancement but rather a result of historical contingencies.